The Oxford Handbook Of Language Attrition (Oxford Handbooks in Linguistics, 2019)
The first handbok dedicated to research into language attrition.The effects of language attrtion can be felt in all aspects of language knowledge, processing and production and can offer unique insights into the mind of bilingual language users.